A documentação pedagógica como uma possibilidade de transformação da pedagogia na Educação Infantil - Furtado, Ana Paula Azevedo (2023)
The main purpose of this study is to analyze the processes of appropriation of Pedagogical Documentation and its possible repercussions on the transformation of pedagogical practices, based on a training intervention in an early childhood education institution. In this thesis, the value of the subjects' participation is seen as a fundamental principle, including that of the children, in the decisions that involve them. That this involvement brings benefits to society as a whole. We see the school as an important environment for the constitution of individuals and we adopt the theoretical perspective that treats Pedagogical Documentation as a complex process made up of other processes which can foster participatory pedagogical practices and thereby change the way we conceive of pedagogy and education. The research has a qualitative approach, of the action-research type, according to Thiollent (2011), which allowed for dialogic actions with all those involved with a view to solving problems, raising awareness and awareness and the production of knowledge (THIOLLENT, 2011). It took place through interviews, observations and formative dialogues. The pedagogical that underpin this thesis are Pedagogical Documentation, Participatory Pedagogies, Childhood Pedagogy and the recomposition of pedagogical practices. The field experience with the participating professionals revealed the existence of initial movements of elaboration of new ways of developing pedagogical practices, but also revealed the maintenance of conceptions present in theoretical models centered on transmission and that it is still necessary to interrogate the learning journeys undertaken in Early Childhood Education institutions. The appropriation of the process of Pedagogical Documentation proved to be a complex and subjective path, treaded differently by each teacher, but in all ways presented evidence of progress in reflections on childhood and the relationships important to be experienced in the collective space of the institution. We believe that it is imperative to review the format of the continuing education courses carried out by the various municipal networks, so that they contribute to breaking down the knowledge that remains from transmissive transmissive models, taking into account the need for teachers to become more teachers to get to know each other better, to become aware of their educational practices and the possibility of reconstructing them.